Vehicular Fog Computing: The Need for a New Paradigm and its Issues - Sri Gnana Deepika, G; Sai Kiran, P (International Journal of Engineering and Technology, 2018)
Smart vehicles participating in VANET have high computing capabilities which lead the demand to support more applications that give safety and effective measures to people. The vehicles in VANET are taking the help of cloud services for communication, computation and storage which benefits in economical way and we call that as vehicular cloud computing (VCC). Due to certain limitations in VCC and also demand for more quality of service applications in smart vehicles a new paradigm called vehicular fog computing (VFC) is proposed which helps to overcome limitations in VCC and provide more quality services to users participating in VANET. Some of the security challenges and possible attacks in VFC are also stated.Â Â